2018
DOI: 10.1111/jocn.14597
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis and validity of the Polish version of the Peritraumatic Distress Inventory in mothers of seriously ill children

Abstract: All parents of hospitalised children are at risk of distress so personnel should pay attention to that and report to a clinical psychologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Cronbach's α coefficient for the entire scale, in the validation group of employees of the Polish emergency medical system, was 0.77. In this group, there was a strong positive correlation between peritraumatic distress and severity of posttraumatic stress symptoms, which confirms the validity of the tool [55]. In our research group, PDI showed strong internal consistency, with a Cronbach's α of 0.83 for the total scale, 0.87 for the Negative Emotions subscales, and 0.80 for the Sense of Threat and Somatic Reactions subscales.…”
Section: Research Toolssupporting
confidence: 79%
See 1 more Smart Citation
“…Cronbach's α coefficient for the entire scale, in the validation group of employees of the Polish emergency medical system, was 0.77. In this group, there was a strong positive correlation between peritraumatic distress and severity of posttraumatic stress symptoms, which confirms the validity of the tool [55]. In our research group, PDI showed strong internal consistency, with a Cronbach's α of 0.83 for the total scale, 0.87 for the Negative Emotions subscales, and 0.80 for the Sense of Threat and Somatic Reactions subscales.…”
Section: Research Toolssupporting
confidence: 79%
“…Peritraumatic distress is defined as the emotional and physiological distress experienced during and/or immediately after a traumatic event and is associated with the development and severity of posttraumatic stress disorder (PTSD) and related psychological difficulties [ 54 ]. The Polish version of the inventory used for mothers of healthy children and children with an eventful perinatal history consists of 11 statements, which make up 2 factors: (1) Negative emotions, (2) Sense of threat and somatic reactions [ 55 ]. Cronbach’s α coefficient for the entire scale, in the validation group of employees of the Polish emergency medical system, was 0.77.…”
Section: Methodsmentioning
confidence: 99%
“…The second factor ‘perceived life threat and bodily arousal’ explained 15% of the variance and had six items. A two-factor structure was also showed in most versions of the PDI (Bui et al, 2011 ; Jehel et al, 2005 ; Rybojad et al, 2018 ). However, the Polish version, validated on a sample of 100 emergency HCWs presented a three factor models (Rybojad & Aftyka, 2018 ), whereas a study on 75 survivors of the 11 September terroristic attack reported a four-factor one (Simeon, Greenberg, Knutelska, Schmeidler, & Hollander, 2003 ).…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, recent prospective data suggest that peritraumatic distress is a stronger predictor of the development of PTSD symptoms than peritraumatic dissociation (Bui et al., 2010 ). Due to its utility in clinical and research setting, the tool was validated in various languages (Jehel, Brunet, Paterniti, & Guelfi, 2005 ; Kianpoor et al, 2016 ; Nishi et al, 2009 ; Rybojad & Aftyka, 2018 ) and in particular populations, such as children (Bui et al, 2011 ), elderly (Bui et al, 2010 ; Brunet et al, 2013 ), caregivers (Rybojad, Aftyka, & Samardakiewicz, 2018 ) or HCWs, (Rybojad, Aftyka, & Milanowska, 2019 ). To the best of our knowledge, to date there are no official validations of the PDI in Italian.…”
Section: Introductionmentioning
confidence: 99%
“…Factor analyses of the PDI have generally resulted in inconsistent findings (Brunet et al, 2001; Rybojad et al, 2018; Simeon et al, 2003). Our ESEM results confirm the likely heterogeneity of the PDI because there were some high-loading items on each of the five factors.…”
Section: Discussionmentioning
confidence: 99%